Hubungan Self-concept dan Self-esteem dengan Kecenderungan Nomophobia pada Siswa SMP - Fitriana, Dyah Ayu Alfida Nur; Sari, Nina Permata; Ildiyanita, Rizky (citeus, 2025)
Since the Covid-19 pandemic, junior high school students tended to be nomophobic due to high smartphone use. This study analyses the relationship between self-concept and self-esteem with nomophobia tendencies in third-grade junior high school students. The approach used is a quantitative approach and a type of correlation research with data collection tools in the form of questionnaires. There were 118 subjects involved who were selected using saturated sampling techniques. Data analysis techniques use rank spearman dan multiple regression. The results show that there is a relationship between self-concept and self-esteem and the tendency to nomophobia in junior high school students.